Premia za inwestowanie w spółki o podwyższonym ryzyku w czasie kryzysu - Homa, Magdalena; Mościbrodzka, Monika (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2016)
In the classical assets pricing model is evaluated the ability to manage, including the identification of individual assets that are undervalued or overvalued in relation to the assets to reflect the market situation. This ability is extremely important in the context of investments made during the crisis and means that the manager in selecting the assets in the portfolio should undertake an analysis of risks inherent in individual securities, focusing not only on the risk of the market. The study proposes the use of the classical and Fama-French three-factor model for the assessment of the risks of investing in companies with a higher risk. They verified their usefulness and examined whether Poland predict changes in the prices of individual assets or selectivity of securities and investments in companies with a higher risk, ie. small caps and the potential value is rewarded.
Keywords: investment risk; equity funds; Fama-French three factor model; CAPM model